Minimizing Evaporation Losses from Small Reservoirs (Wadi Houran-case study) - I. Naif a, Rasha; Abdulhameed, Isam M. (Anbar Journal of Engineering Sciences, 2021)
minimizing the surface area of a reservoir during maximum evaporation losses period. A mathe-matical relationship linking the depth of water with the surface area of the reservoir has been formulated, and its integration can be used to estimate conservable water quantities. Reducing the water level in the reservoir to the minimum permissible level before the dry months has re-duced the evaporation losses by 65% and 51% for the two scenarios. These two scenarios have been conducted by assuming that the dry months start with the presence of the water level in the reservoir at a height of 14 and 12 m, respectively. On the other hand, evaporation losses during drought months have been decreased by 24%. By this technique, it can be possible to obtain wide areas suitable for agriculture, contributing to the economic and social development of the region. Also, Depth index(DI) suggested in this study and defined as the ratio of volume of the water in the reservoir to corresponding surface area, to compare the location of the best dam among the 13 proposed dams in Wadi Houran by reducing evaporation losses. The results of this index showed the best location was at DI=10.901 in DM 7, and the worst is at DI=2.425 in DM 8.